Chaotic Motions of the Duffing-Van der Pol Oscillator with External and Parametric Excitations - Liangqiang Zhou; Fangqi Chen (Shock and Vibration)
The chaotic motions of the Duffing-Van der Pol oscillator with external and parametric excitations are investigated both analytically and numerically in this paper. The critical curves separating the chaotic and nonchaotic regions are obtained. The chaotic feature on the system parameters is discussed in detail. Some new dynamical phenomena including the controllable frequency are presented for this system. Numerical results are given, which verify the analytical ones.